Association of E-cadherin (CDH1) gene polymorphisms and gastric cancer risk - Al-Moundhri, Mansour S (Baishideng, 2010)
AIM: To investigate the associations between CDH1 gene polymorphisms and gastric cancer (GC) risk predisposition. METHODS: We analyzed four CDH1 polymorphisms (+54 T>C, -160 C>A, -616 G>C, -3159 T>C) in an Omani population, by extraction of genomic DNA from the peripheral blood of 192 patients with GC and 170 control participants and performed CDH1 genotyping using DNA sequencing. RESULTS: CDH1 -160 -AA genotype was associated with an increased risk of GC (OR = 3.6, 95% CI: 1.1-11.8) (P = 0.03). There was no significant association between the other polymorphisms and GC risk. The haplotype analysis of +54 T>C, -160 C>A, -616 G>C, -3159 T>C genotypes revealed that the OR of CCGC and CAGC haplotypes was 1.5 (95% CI: 0.7-3.5) and 1.5 (95% CI: 0.2-3.0), but did not reach statistical significance. CONCLUSION: The current study suggests that the -160 AA genotype was associated with an increased risk of GC in Oman.